Evaluation of Antimicrobial, Antioxidant, Cytotoxic and DNA Protective Effects of Oyster Mushroom: Pleurotus pulmonarius (Fr.) Quel. - Akyuz, Mehmet; Inci, Sule; Kirbag, Sevda (Springer Heidelberg, 2023)
Due to climate change and economic difficulties, food production and supply in the world is getting harder and harder. The importance of edible mushrooms is increasing day by day due to their consumption as food, nutritional value and health benefits. Many types of mushrooms are cultivated to overcome the difficulties of obtaining them naturally. Among the mushrooms cultivated in the world, the Pleurotus species ranks second after Agaricus spp. The aim of the current research was to determine the antimicrobial, antioxidant, cytotoxic and deoxyribonucleic acid protective effects of Pleurotus pulmonarius (Fr.) Quel. grown on some local cellulosic wastes. The antimicrobial activity and the minimum inhibitory concentration (MIC) tests carried out by the disk diffusion method and macro-broth dilution techniques. Antioxidant activity was ascertained by the radical scavenging capacity method of 2.2-diphenyl-1-picrylhydrazil. Total antioxidant status and total oxidant status of P. pulmonarius extracts were determined with rel assay kits. The DNA protective effect was evaluated using plasmid pBR322 DNA treated with ultraviolet (UV) and H2O2, and also the cytotoxic effects on the human lung cancer cell (A549) and human breast cancer cell (MDA-MB-231) lines were evaluated using the 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay method. It was observed to be highly active against all pathogen bacteria (except S. mutans) and dermatophytes (Epidermophyton sp. and Trichophyton sp.) (14.0-29.3 mm) compared to the control group (10.0-32.7 mm), but low against Candida tropicalis. It also showed significant antioxidant potential, the highest TAS (1.33 mmol/L) and TOS (6.74 mu mol/L) values were obtained in the mixture of Medicago sativa + Populus nigra (MS-PS (1:1)), on Medicago sativa (MS) medium, and also DPPH radical scavenging effect was more effective at 25 mg (68.09%) on MS-PS (1:1) medium. The methanol extract of P. pulmonarius cultured on MS-PS (1:1) at a concentration of 400 mu g/ml significantly reduced the percent viability in MDA-MB-231 cell lines (1.41%). However, it was determined that P. pulmonarius did not have a DNA protective effect. As a result, it was observed that P. pulmonarius had strong antimicrobial, antioxidant and cytotoxic activities, but did not have a DNA protective effect.
Keywords: Pleurotus pulmonarius; Medicinal effects; Edible mushroom; Cultivation